HUBUNGAN INTENSITAS MEMBACA DENGAN KETERAMPILAN MENULIS CERITA PADA SISWA KELAS IV SD - Nasty Minarsih; Rien Anitra; Mertika (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article discusses a study regarding the relationship between reading intensity and story writing skills. The research method used is correlation research with a quantitative approach. The research population involved all fourth-grade elementary school students. The sampling technique used a random sampling technique with the formula of Isaac and Michael with the number of 78 students. Data collection techniques were based on questionnaire and measurement techniques, namely using reading intensity questionnaires and story writing skills tests. The data analysis technique used was Product Moment Correlation. The results showed that 1) the level of students' reading intensity was classified as good in the medium category with an average value of 44.69, 2) the level of story writing skills was categorized as good with an overall average of 59.5, and 3) there was a relationship between reading intensity and story writing skills with an average score of 5.89, with a correlation value of 0.56, and a coefficient of determination with an average score of 31.36%. Based on the results of the research that has been done, therefore, there was a relationship between reading intensity and story writing skills.